Native fungi as metal remediators: Silver myco-accumulation from metal contaminated waste-rock dumps (Libiola Mine, Italy). Issue 3 (4th March 2017) - Cecchi, Grazia; Marescotti, Pietro; Di Piazza, Simone; Zotti, Mirca
ABSTRACT: Metal contamination constitutes a major source of pollution globally. Many recent studies emphasized the need to develop cheap and green technologies for the remediation or reclamation of environmental matrices contaminated by heavy metals. In this context, fungi are versatile organisms that can be exploited for bioremediation activities. In our work, we tested silver (Ag) bioaccumulation capabilities of three microfungal strains ( Aspergillus alliaceus Thom & Church, Trichoderma harzianum Rifai, Clonostachys rosea (Link) Schroers, Samuels, Seifert & W. Gams) isolated from a silver polluted site. The aim was to select silver tolerant native strains and test their potential silver uptake. Among the three species tested, T. harzianum was the most efficient strain to tolerate and accumulate silver, showing an uptake capability of 153 mg L −1 taken at the Ag concentration of 330 mg L −1 . Our study highlights the potential use of native microfungi spontaneously growing in sulphide-rich waste rock dumps, for silver bioaccumulation and bioremediation.